Targeting the aryl hydrocarbon receptor by gut phenolic metabolites: A strategy towards gut inflammation - Pinto, CJG (2023)
The Aryl Hydrocarbon Receptor (AHR) is a ligand-dependent transcription factor able to control complex transcriptional processes in several cell types, which has been correlated with various diseases, including inflammatory bowel diseases (IBD). Numerous studies have described different compounds as ligands of this receptor, like xenobiotics, natural compounds, and several host-derived metabolites. Dietary (poly)phenols have been studied regarding their pleiotropic activities (e.g., neuroprotective and anti-inflammatory), but their AHR modulatory capabilities have also been considered. However, dietary (poly)phenols are submitted to extensive metabolism in the gut (e.g., gut microbiota). Thus, the resulting gut phenolic metabolites could be key players modulating AHR since they are the ones that reach the cells and may exert effects on the AHR throughout the gut and other organs. This review aims at a comprehensive search for the most abundant gut phenolic metabolites detected and quantified in humans to understand how many have been described as AHR modulators and what could be their impact on inflammatory gut processes. Even though several phenolic compounds have been studied regarding their anti-inflammatory capacities, only 1 gut phenolic metabolite, described as AHR modulator, has been evaluated on intestinal inflammatory models. Searching for AHR ligands could be a novel strategy against IBD.